Pengaruh Pelayanan Daring dan Ketepatan Waktu Pelayanan terhadap Kepuasaan Pelanggan BPRS AL Salaam Cilengsi Bogor - Lies Sunarmintyastuti; Hanggono Arie Prabowo; Loecita Sandiar; Hugo Aries Suprapto; Lengsi Manurung; Iramdan Iramdan (Jurnal Ilmiah Wahana Pendidikan, 2021)
The purpose of this study was to determine the effect of online service and timeliness of service on customer satisfaction at BPSR Al Salam. The background of this research is online services that have been booming lately, influenced by the ongoing Corona pandemic. For this reason, many financial institutions have changed face-to-face services to online services. This raises many problems and adaptation is not easy. This research uses quantitative methods. Researchers used SPSS 20 to process the data. Data is taken from a questionnaire. The data were processed by classical test, heteroscedasticity and multicollinearity test. After being tested classically, the data was continued with multiple regression test. The sample used is the customers of BPRS Al Salam. The data collection method used the simple random sampling method. Samples were taken randomly from the entire existing population. The researcher used the normality test for the homogeneity test, the multiple linear test and the coefficient of determination test. The results show that online service affects customer satisfaction, timeliness of service affects customer satisfaction, online service and timeliness of service simultaneously affect customer satisfaction